Regulation of somatostatin expression by vitamin D3 and valproic acid in human adipose-derived mesenchymal stem cells - Doering, Luise (Stem Cell Res Ther, 2019)
BACKGROUND: Adipose-derived mesenchymal stem cells (ADMSC) are non-haematopoietic, fibroblast-like multipotent progenitor cells. They have the potential for trilineage (adipocyte, chondrocyte and osteocyte) differentiation as well as differentiation into endocrine pancreatic progenitors. In diabetic or cancer therapy, somatostatin (SST) expression plays a vital role. Small molecules such as valproic acid (VPA) and micronutrients like vitamin D3 have differentiation potential in ADMSC. Therefore, the aim of this study was to investigate the role of vitamin D3 machinery and its metabolic enzymes in ADMSC. Furthermore, the reprogramming effect of vitamin D3 and VPA was evaluated on somatostatin expression in pancreatic lineage differentiation. METHODS: ADMSC were characterised based on their cell surface marker profile using flow cytometry. Specific adipogenic and osteogenic differentiation protocols were used in this study. Gene expression of several pluripotent, endodermal, pancreatic progenitor and pancreatic endocrine lineage markers were investigated in native ADMSC and after stimulation with different concentration of vitamin D3 for five consecutive days (0, 50, 100, 150 nM) and VPA (0.5, 1, 1.5, 2 mM) by real-time PCR. Furthermore, somatostatin expression was confirmed with ELISA and immunocytochemistry. RESULTS: In ADMSC, the expression of somatostatin mRNA, the vitamin D receptor (VDR) and its metabolising enzymes 1 α-Hydroxylase, 24-Hydroxylase and 25-Hydroxylase were detected. Upon stimulation with vitamin D3, nuclear translocation of vitamin D receptor (VDR) was observed. Interestingly, the presence of vitamin D3 reduced the transcription of the somatostatin gene. By contrast, VPA treatment of cultivated ADMSC showed enhancing effect on somatostatin gene expression. No other pluripotent, endodermal, pancreatic progenitor or pancreatic endocrine lineage mRNA expression was modulated under the influence of vitamin D3 and VPA. CONCLUSION: Human ADMSC carry the VDR. The vitamin D metabolising enzyme 25-Hydroxylase responded to the addition of vitamin D3. Moreover, our results demonstrate that somatostatin expression in ADMSC is constitutive, partially secreted and regulated by vitamin D3 and VPA.